PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMPN 3 RAMBAH SAMO - Mustafa, Satria Riki; Afri, Lusi Eka; -, Nurrahmawati (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of this research was to observe the effect of Numbered Heads Together (NHT) cooperative learning model onstudentâs mathematic learning outcomes of student of 8th grade Junior High School 3 Rambah Samo. The type of this research wasa Quasi experimental with The Randomized Control Group Only Design. The population in this research were all class 8th gradeJunior High School 3 Rambah Samo. Sampling was done by random sampling, so the class VIII A selected as experimental classand the class VIII B as a class control. Based on the hypothesis testing performed by t test obtained t = 2,348 and t = 2,011. Thismeans that > , then is rejected. This means that there were differences between the experimental class and thecontrol class. It can be concluded that there effect of the experimentation of cooperative learning model Numbered Heads Together(NHT) to the mathematic learning outcomes of student of 8th grade Junior High School 3 Rambah Samo.